Adapting the Accelerated Solvent Extraction Method for Resin and Rubber Determination in Guayule Using the BÜCHI Speed Extractor - Rozalén, Juana (Molecules, 2021)
Guayule (Parthenium argentatum Gray) is a promising alternative source to Hevea brasiliensis for the production of natural rubber, which can reach levels of 8–9% under industrialized farming conditions. The most common method for determining rubber concentration is by accelerated solvent extraction (ASE), a technique developed by the Dionex Corporation and almost exclusively performed with the Dionex ASE-200 or 350 systems. Herein, it is sought to apply and adapt the most common methods used in the literature for the Dionex system to another extraction platform, the BÜCHI Speed Extractor E-914. Results showed that using a sand sandwich method to confine the sample in the center and exploiting a larger cell volume (80 mL) for extraction prevents the occurrence of overpressure and problems with clogging. Under optimized conditions, the coefficient of variation was <15% for both resin quantification for samples containing 5.0–15.8% of resin and for rubber quantification for samples with 1.7–10.3% rubber content. The extraction time for resin (2 cycles of 5 min each) was smaller than for rubber (2 cycles of 20 min each). It would be interesting to carry out interlaboratory comparisons to standardize the method at an international level.